S47 Impact of number of sampling sites and specimen dimension on the performance of nuclear grade and growth patterns in predicting survival in epithelioid malignant pleural mesothelioma: a single institution review of 614 cases. (12th November 2019) - Zhang, YZ; Brambilla, C; Molyneaux, PL; Rice, A; Robertus, JL; Jordan, S; Lim, E; Lang-Lazdunski, L; Begum, S; Dusmet, M; Anikin, V; Beddow, E; et al.
Abstract : Introduction: There is limited evidence regarding the optimal number of sampling sites and specimen dimension in histological diagnosis of malignant pleural mesothelioma (MPM). Previously we have validated 2-tier nuclear grade as an independent predictor of survival in epithelioid MPM. This study evaluates the association between sampling parameters and the performance of 2-tier nuclear grade and growth pattern as survival predictors using a biopsy-heavy cohort. Methods: Clinicopathological information including the number of sampling sites, tissue dimension, 2-tier nuclear grade, predominant growth pattern and overall survival (OS) were retrieved from an institutional mesothelioma database comprising 614 consecutive cases of epithelioid MPM over a 15 year period. Survival analysis was performed using Kaplan-Meier method. Association between categorical variables was analysed using Fisher exact test, and was assessed in relation to biopsy size and number. Statistical significance was defined as p <0.05. Results: The mean age was 69.1 years, with male preponderance (75.6%). 87.0% (534/614) received biopsy only. The median number of sites sampled was 1 (range 1–20). The median maximum tissue dimension was 18 mm for biopsies (range 2–140 mm) and 145 mm for resections (range 40–350 mm). 17.7% of all biopsies (95/534) were taken from a single site with a maximum dimension of ≤10 mm (median: 8 mm). Low grade tumours showed significantly prolonged OS compared with high grade (19.3 months vs. 8.9 months, p <0.001). Overall, the median OS of our cohort was 14.7 months. 2-tier nuclear grade predicted OS independent of age, type of procedure, necrosis and atypical mitosis ( p =0.001). Growth pattern was not an independent predictor of OS ( p =0.152). This 2-tier nuclear stratification lost predictive power in the setting of single site biopsy, ≤10 mm maximum dimension ( p =0.572). We observed 'grade-shift' phenomenon as more high grade disease was detected with increasing number of sampling sites (up to 3 sites, p <0.001) and maximum tissue dimension (≥20 mm, p =0.017). The impact on assessing growth pattern was less pronounced in comparison. Conclusions: We propose an optimal sampling standard of 3 sites or a maximum tissue dimension of ≥20 mm from a single site. This then allows a 2-tier nuclear grading system to provide prognostic stratification for clinical care and research of epithelioid MPM.